Development of a pre-cooked nutraceutical cake from biofortified vegetables for older people - Fernández-Cordero, Pamela (2018)
The generational transition experienced by the Costa Rican population has driven the approach of various strategies to improve nutrition and life quality of elder people. On this concern, the development of special food products is encouraged in the food industry to accomplish this demand, so the objective of this work was a nutraceutical food product based on biofortified sweet potato (Ipomoea batatas) and cassava (Manihot esculenta) and, pejivaye (Bactris gasipaes). On the first stage of the development of this product, a 60g pre-cooked frozen cake was elaborated. This cake was selected due to nutritional purposes, market trends and innovation from a list of fourteen possible products to develop. In the next stage, the process and formulation were defined. Finally, a chemical analysis was performed to compare the raw materials and the finished product. This comparison allowed determine that this cake covers between 30 and 38% of the daily requirements of vitamin A in the Costa Rican senior citizens.